Responsibility definition and standard calculation of forest horizontal ecological compensation: a case study of Chongqing, China - Yu, Honghong; Li, Suwan; Yang, Jiameng (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe work of forest horizontal ecological compensation has progressed from policy guidance to practical exploration. Scientifically defining the responsible entities and measuring the compensation standard is an important component of improving the forest horizontal ecological compensation mechanism.MethodsThis study selects Chongqing as a case study. From the perspective of the carbon budget, the carbon emissions, forest carbon sequestration, and non-forest carbon sequestration of 38 districts and counties in Chongqing were measured. Additionally, by incorporating carbon market transaction prices, economic development levels, and resource endowment conditions of different regions, the forest horizontal ecological compensation standards for each district and county were calculated.ResultsFrom 2012 to 2021, the payer and receiver entities for forest horizontal ecological compensation in Chongqing generally remained stable, overall presenting a spatial pattern of “southwest compensating the east.” The total compensation amount that forest ecological protection areas in Chongqing should receive showed a steady increase from 2012 to 2021. The total compensation amount that ecological payment areas should pay showed a fluctuating upward trend. The spatial distribution of forest horizontal ecological compensation priorities in Chongqing changed significantly.DiscussionThe issue of carbon supply and demand mismatch exists in various districts and counties in Chongqing, therefore it is essential to further clarify the forest compensation responsibility based on the carbon budget of each district and county. Taking into account the ecological characteristics of forests, carbon supply and demand, economic development level, as well as other factors, differential regional compensation standards should be established to achieve a synergistic symbiosis between regional forest ecology and economic development.